"Models of conversion in Modern English" - (:unkn) unknown (Rubanets Tetyana, 2024)
The article under studies deals with the issue of the conversives structure and semantic characteristics in the models noun – verb, verb – noun, noun – adjective and adjective – noun. It consists of four stages. The first stage regards the main approaches to the phenomenon of conversion in line with system-structural, communicative-functional and cognitive paradigms, as well as elaborates the definitions, used in the work. The purpose of the second stage is to form the research material. By a continuous sample of three academic dictionaries New Webster’s Dictionary of the English Language (2009. 5th ed. London: Pearson education), Macmillian English Dictionary (2006. In M. Rundell (ed.), For advanced learners. London: Palgrave Macmillan) and Longman Dictionary of Contemporary English (2009. 5th ed. London: Pearson education), a total amount of 18,263 conversives was written out. To avoid repeating the conversives given in the dictionaries, we have developed a sample, in which every conversion pair occurred once. The total number of the studied conversives is 10,140 tokens, grouped into 5,070 conversion pairs. The third stage highlights the structural and semantic features of conversives in modern English. It describes the peculiarities of parts of speech and semantic transitions, as well as determines the conversives structural models and their modifications. In order to establish regular semantic changes, the conversion semantic models are singled out, quantitative characteristics of each model are established and the most productive transitions from the genera- tive to the derivative are described. At the final stage, the results of the work are summarized and the prospects for further research are outlined. The obtained results will enrich the theory of nomination with the new systematized material of conversives, which are an integral part of natural languages, and the analysis of English language conversives will supplement the theoretical and methodological basis for further study of the phenomenon of conversion in other languages.
Keywords: conversion; conversive; lexical-semantic groups; semantic analogy; transposition; word formation